(untitled) (Archive of Conferences, 2020)
At the end of the 20th and beginning of the 21st centuries, fundamental changes took place in the methodology of science. The complication of the world means that it has become clear that the traditional methodology of science (for example, reductionist methodology) cannot adequately reflect the knowledge of its laws. Therefore, it became necessary to develop alternative methods for studying the phenomenon of complexity.